Pengukuran Kinerja Keuangan Pada Perusahaan Startup : Studi PT GoTo Gojek Tokopedia Tbk Periode 2020-2022 - Aninda Ira Musikawati; Ratri Paramitalaksmi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The growth of the digital world greatly influences the national economy and has a positive impact on the business world in the fields of technology and information. Tthis research intends to analyze financial reports in measuring financial performance in startup companies. The sample used in this research was PT GoTo Gojek Tokopedia Tbk. The data used is quantitative descriptive with secondary data published by the Indonesian Stock Exchange for the 2020-2022 period. This research analysis uses financial ratio formula calculations consisting of liquidity ratios, laverage ratios, activity ratios, and profitability ratios as analytical tools used to measure the financial performance of startup companies. The results of the research show that the company liquidity performance is classified as very good, the activity ratio is classified as good in the total assets turnover ratio, is classified as poor, and the profitability ratio shows a fairly good level of profit generation.